Stability and Bifurcation Analysis of an Amensalism Model with Weak Allee Effect - Wei, Zhen; Xia, Yonghui; Zhang, Tonghua (Qualitative theory of dynamical systems, 2020)
In this paper, an amensalism model with weak Allee effect is proposed. The existence and stability of all possible positive equilibria and the possible boundary equilibria of the system are investigated. We also prove that there are two saddle-node bifurcations under suitable conditions by Sotomayor’s theorem. An example with its numeric simulations are given to verify our main results.